Certainty vs. severity revisited: evidence for Colombia (2016)
A recurring debate in the literature on crime control is whether an increase in the probability of punishment is a more effective deterrent than an increase in the severity of the sanction. This paper further explores this issue in the context of crime in Colombia. We use a natural policy experiment (the introduction of the Adversarial System of Criminal Justice) to estimate how changes in the costs associated with criminal activity have affected crime rates in the country. The results show that for the Colombian case, when a reform reduces the probability of punishment it leads to an increase in crime rates across a variety of different types of criminal activity, including both violent crimes and property theft. Moreover, our evidence suggests that changes in the probability of punishment have greater impact in crime rates than changes in its severity. This has important implications for public policy regarding crime rates and the design of judicial mechanisms.